Viscosity model for aluminosilicate melt - Zhang G.H.; Chou K.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The structurally based viscosity model proposed in our previous study is extended to include more components, e.g. SiO2, Al2O3, FeO, MnO, MgO, CaO, Na2O and K2O. A simple method is proposed to calculate the numbers of different types of oxygen ions classified by the different cations they bonded with, which is used to characterize the influence of composition on viscosity. When dealing with the aluminosilicate melts containing several basic oxides, the priority order is established for different cations for charge compensating Al3+ ions, according to the coulombic force between cation and oxygen anion. It is indicated that basic oxides have two paradox influences on viscosity: basic oxide with a higher basicity decreases viscosity more greatly by forming weaker non-bridging oxygen bond; while it increases viscosity more greatly by forming stronger bridging oxygen bond in tetrahedron after charge compensating Al3+ ion. The present model can extrapolate its application range to the system without SiO2. Furthermore, it could also give a satisfy interpretation to the abnormal phenomenon that viscosity increases when adding K2O to CaO-Al2O3-SiO2 melt within a certain composition range.